2019
DOI: 10.1093/nar/gkz873
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of sequence specific NF-κB DNA binding and transcription by IKKβ phosphorylation of NF-κB p50 at serine 80

Abstract: Phosphorylation of the NF-κB transcription factor is an important regulatory mechanism for the control of transcription. Here we identify serine 80 (S80) as a phosphorylation site on the p50 subunit of NF-κB, and IKKβ as a p50 kinase. Transcriptomic analysis of cells expressing a p50 S80A mutant reveals a critical role for S80 in selectively regulating the TNFα inducible expression of a subset of NF-κB target genes including pro-inflammatory cytokines and chemokines. S80 phosphorylation regulates the binding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…However, several studies report that SMAD1 interacts with NF-κB1 in overexpression experiments in 293 T cells, and that SMAD1 bound selectively to endogenous NF-κB1 p50 protein in RAW 264.7 cells [ 42 ]. Consistent with these observation, it has been reported that the NF-κB1 p50 homodimer can regulate specific gene expression [ 43 45 ]. In our current study of MM, we found that SMAD1 expression is reduced after NF-κB1 knockdown, and vice versa, suggesting that SMAD1 may contribute to MM progression by activation of NF-κB1.…”
Section: Discussionsupporting
confidence: 74%
“…However, several studies report that SMAD1 interacts with NF-κB1 in overexpression experiments in 293 T cells, and that SMAD1 bound selectively to endogenous NF-κB1 p50 protein in RAW 264.7 cells [ 42 ]. Consistent with these observation, it has been reported that the NF-κB1 p50 homodimer can regulate specific gene expression [ 43 45 ]. In our current study of MM, we found that SMAD1 expression is reduced after NF-κB1 knockdown, and vice versa, suggesting that SMAD1 may contribute to MM progression by activation of NF-κB1.…”
Section: Discussionsupporting
confidence: 74%
“…Using all-atom molecular dynamics simulations, we first establish a DNA-NF-κB system based on the structure of NF-κB p50/p65 heterodimer in a complex with immunoglobulin DNA (PDB entry: 1VKX) (Figure a). The selected DNA segments are 25 base pairs with the sequence of AGCGA­TTTGA­GAAAC­TTCAT­CATCA, which is not a recognized DNA binding site. , Our results demonstrate that the binding of NF-κB molecules substantially suppresses the bending of DNA segments. In the binding region, the DNA bending angle is reduced by a factor of α = 0.82 (Figure d).…”
Section: Unspecific Interactions With Nf-κb Regulate Dna Conformationmentioning
confidence: 81%
“…Literature also suggests that multivalent proteins form larger aggregates in response to increased MMC via self-condensation (Shin and Brangwynne, 2017; Watanabe et al ., 2018; Jalihal et al ., 2020, 2021; Keber et al ., 2021). While free EGFP depicts a non-specific weaker aggregation in the cytoplasm, NFκβ, a protein with DNA binding domain (Yan et al ., 2012; Smith et al ., 2019; Vonderach et al ., 2019), shows globular self aggregation in response to hypertonic shock in NIH/3T3 cells expressing p65-EGFP, a subunit of the NFκβ complex ( Fig S4A-i ). However, in Heclin treated NIH/3T3, NFκβ shows drastically massive, irregularly shaped aggregates ( Fig S4A-ii ) compared to the globular condensates from hypertonic shock.…”
Section: Resultsmentioning
confidence: 99%